Premodification of Nouns in Film Reviews - Paul, Vladimír (Univerzita Pardubice, 2019)
This bachelor thesis is concerned with the use of premodification in the genre of film reviews. The theoretical part introduces the genre of film reviews with an emphasis on its distinctive functions, moreover, the subject of noun phrase is explained as well as various types of premodification. The practical part examines the type, frequency and purpose for the usage of premodification in the context of written film reviews.
Premodifikace podstatných jmen ve filmových recenzích
Keywords: genres; film reviews; noun phrases; premodification; adjectives; žánry; filmové recenze; jmenné fráze; premodifikace; přídavná jména